(untitled) (Al-Qamar, 2021)
Islamization of the political system in the post-partition Pakistan was a foremost desire of the people but the ground realities were totally different. Since its inception as an independent state, Pakistan has experienced different political dispensations including elected ones patronized by dictatorships. Though elections are one of the prerequisites of a democratic system but they are not the only precondition for a system to be democratic. Democratic attitudes, values, and a conducive environment are must for a flourishing democracy. Although General Zia held elections and there was an elected assembly still we cannot term his system as democratic. The system actually strengthened one person: General Zia with the parliament as a rubber stamp. As General Zia lacked legitimacy to rule, he resorted to the so-called Islamic system to get support of the people. He actually used Islam for his political objectives. The religion card enabled him to enjoy the longest military rule in the country.